PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN PAPAN BULETIN TERHADAP HASIL BELAJAR IPAS PESERTA DIDIK KELAS V SD INPRES MINASA UPA - Fitriani; Rufaida, Salwa; Nur, Andi Muafiah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem in this study is the low learning outcomes of students in grade V of SD Inpres Minasa Upa. The purpose of this study is to analyze the influence of bulletin board media on the learning outcomes of students in grade V of SD Inpres Minasa Upa. This type of research is a quasi-experimental (Quasi Experiment). The subjects of the study were students in grade V of SD Inpres Minasa. Data collection techniques were carried out through initial tests (pretest) and final tests (posttest) of learning outcomes. Analysis of research data using descriptive statistical analysis and inferential statistical analysis. The results of the study showed that the average pretest results of students in the experimental class were 49.86, while in the control class it was 45.32, which indicated that the pretest in both groups was in the low category. The posttest results of students in the experimental class obtained an average value of 73.86 and were in the high category, while in the control class obtained a figure of 61.59 and were in the medium category. The results of the hypothesis test show that the significance value obtained is less than 0.05, which indicates that there is an influence of the use of bulletin board media on the learning outcomes of class V students at SD Inpres Minasa Upa.